The Impact of the EU Engagement in Serbia and Albania During the First Wave of the COVID-19 - Bregu, Meljana (European Scientific Journal, ESJ, 2024)
Alongside cooperation and competition, solidarity is a fundamental value of the European Union, the foundation of the Schuman Declaration, and one of the EU’s sustaining pillars. The COVID-19 pandemic tested the value of European solidarity; however, amid this unprecedented crisis, the EU initially failed to determine the most appropriate course of action. This provoked a strong reaction within the European Union and affected the EU’s position in the Western Balkans as a soft power. The EU’s lack of action and the ban on the export of medical supplies caused instantaneous adverse reactions in the region, Serbia in particular. The paper’s purpose is to describe the consequences for Serbia and Albania of the lack of solidarity that characterized the initial surge of the pandemic. The two countries were selected based on their dissimilar foreign policies, the influence of other actors such as China and Serbia, and public opinion concerning European integration. Albania has consistently demonstrated strong support for the European concept, but this support has declined in Serbia in recent years. In addition, the paper examines the distinct effects of Russia’s and China’s actions during the pandemic in Albania and Serbia, respectively. Furthermore, the paper analyses the significant European intervention and aid in Serbia and Albania. Additionally, the study investigates the outcomes of the Balkan Barometer surveys conducted in 2020 and 2021 to assess the influence of the COVID-19 pandemic on support for European integration in Albania and Serbia. It also incorporates various official statements and documents from the European Union and a poll conducted by the International Republican Institute.